News Portal Website Measurement Analysis Using ISO/IEC 25010 And McCall Methods - Satria Budi; Windu Gata; Mohamad Noor; Supriadi Pangabean; Cicih Sri Rahayu (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
Information system is an asset for a company when the information system is managed properly. In the past, newspapers have become one of the main sources for people who want to get the latest news about what is happening around them. But now, the important role of newspapers is gradually being replaced by online-based news portals that can deliver news very quickly. PT Info Pena Indonesia itself utilizes an information technology in carrying out the process of managing and disseminating the news they produce with the help of a web portal called Jitunews. This research is quantitative in nature, namely explaining the use of survey methods by distributing questionnaires to users of the Jitunews news portal site for data about the characteristics of the ISO/IEC 25010 and McCall methods. The results of the research conducted on the backend and frontend pages show that the Jitunews website deserves a